Governing (through) religion: Reflections on religion as governmentality. (November 2016) - Ali Nasir, Muhammad
This inquiry examines the question how the category of 'religion' generates a complex form of power oriented to the government of subjects. It does this through a critical reading of the right to freedom of religion, offered from the perspective of governmentality. It is argued that the right to freedom of religion enables the rational goals of government to relate to religiosity in such a manner that those subject to them (religious qua juridical) are made at once freer and more governable 'in this world'.